Disinformation in Educational Environments: A Case Study in Vocational High Schools - M. Yakub Iskandar; Albizar Albizar; Yusrial Yusrial; Reza Saputra; Anadya Diva Vanessa (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2026)
The rapid development of digital technology has transformed the information ecosystem, increasing both access to information and vulnerability to disinformation, particularly within educational environments where students often have limited digital literacy skills. This study aims to analyze the dynamics and impacts of disinformation through a case study at Vocational High School 1, Solok City. Employing a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis with triangulation to ensure validity. The findings reveal that disinformation regarding study tour fees, disseminated by a student, resulted in the cancellation of the activity, financial losses, erosion of trust in the school institution, and psychological impacts on students. These results highlight the significant vulnerability of school communities to disinformation, especially in contexts characterized by strong interpersonal trust and limited verification practices. The study emphasizes the importance of strengthening digital literacy through curriculum integration, school literacy programs, and the role of libraries, alongside the need for effective regulatory frameworks and the accountability of Electronic System Providers (ESPs). Ultimately, addressing disinformation requires a multi-stakeholder approach involving government, educational institutions, civil society, and digital platforms to build sustainable societal resilience in the digital era.